Ambiguity in the Movie “Titanic” by James Cameron: Semantics Analysis - Indah Putri Ladini; Heri Heryono (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aimed to analyze and examine the types of ambiguity in the branch of linguistics, and semantics in the movie “Titanic” by James Cameron and also examine the meaning of that word or sentence that makes it ambigous. The method is used in this analysis is the quantitative analysis method. The data was used taken from some journals, books, and from the movie “Titanic” which was released in 1997. Ambiguity and vagueness could be viewed as opposite ends of a continuum, with polysemy in the middle, according to the Cognitive Grammar framework (Langacker 1987). The results demonstrated that there are two types of meaning found, namely Lexical Ambiguity (65%) and Syntactic Ambiguity (35%). The data was obtained from the results of processing data and reading several sources of existing journals.